Answer:
it is the second one
Step-by-step explanation:
Answer:
-8
Step-by-step explanation:
-8×-3 =24 thats yeaaaa
Here u go the answer is 4/3
Answer:
x = ± 1 , x = ± ![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
Step-by-step explanation:
Let u = x² , then
- 3x² + 2 = 0 , can be expressed as
u² - 3u + 2 = 0 ← in standard form
(u - 1)(u - 2) = 0 ← in factored form
Equate each factor to zero and solve for u
u - 1 = 0 ⇒ u = 1
u - 2 = 0 ⇒ u = 2
Change the variable u back to x
x² = 1 ( take square root of both sides )
x = ± 1
or
x² = 2 ( take square root of both sides )
x = ± ![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
Answer:
b. y = 3(x+2)^2 + 5
Step-by-step explanation:
The vertex form of a parabola is
y = a(x - h)^2 + k where (h, k) is the vertex.
Here h = -2 and k = 5 so the following could be the required equation\;
y = 3(x+2)^2 + 5